Fabrication of colloidal silver-peptide nanocomposites for bacterial wound healing - Ovais, Muhammad; Ali, Arbab; Ullah, Sana; Khalil, Ali Talha; Atiq, Atia; Atiq, Maria; Dogan, Nurcan; Shinwari, Zabta Khan; Abbas, Manzar (ELSEVIER, 2022)
Increased antibiotic resistance has become a real healthcare challenge for humanity. Several novel approaches for the formation of nanomaterials have been developed to tackle different bacterial strains and wound disinfection. Short peptide modulated metal nanomaterials have gained attention because of their biocompatibility and ability to reduce metal ions in-situ to form nanoparticles. Here we have used a short peptide conjugate as a reducing and capping agent to make stabilized silver-peptide composite nanoparticles under mild UV light exposure. This photochemical method is one of the green approaches and reduces the toxic effects of chemicals that are often used in traditional synthetic strategies. These composite nanoparticles demonstrated promising activity against Escherichia coli and Staphylococcus aureus at an in-vitro level and have the ability to cure wounds disinfections in-vivo. Furthermore, these composite nanoparticles show excellent biocompatibility, and no side effects were observed in liver enzymes and organs, in a histopathology study. Such a simple strategy of sustainable supramolecular chemistry could help develop novel nanomaterials as potential antibiotic agents of the future.
Keywords: Short peptide; Metal-composites; Antibacterial; In-vivo wound healing; Wound disinfection; NANOPARTICLES; REDUCTION; Chemistry